A taxonomy of chemicals of emerging concern based on observed fate at water resource recovery facilities. (March 2017) - Jones, Steven M.; Chowdhury, Zaid K.; Watts, Michael J.
Abstract: As reuse of municipal water resource recovery facility (WRRF) effluent becomes vital to augment diminishing fresh drinking water resources, concern exists that conventional barriers may prove deficient, and the upcycling of chemicals of emerging concern (CECs) could prove harmful to human health and aquatic species if more effective and robust treatment barriers are not in place. A multiple month survey, of both primary and secondary effluents, from three (3) WRRFs, for 95 CECs was conducted in 2014 to classify CECs by their persistence through conventional water reclamation processes. By sampling the participating WRRF process trains at their peak performance (as determined by measured bulk organics and particulates removal), a short-list of recalcitrant CECs that warrant monitoring to assess treatment performance at advanced water reclamation and production facilities. The list of identified CECs for potable water reclamation (indirect or direct potable reuse) include a herbicide and its degradants, prescription pharmaceuticals and antibiotics, a female hormone, an artificial sweetener, and chlorinated flame retardants. Highlights: Primary and secondary effluents were analyzed for three WRRFs under dry conditions in Texas and Oklahoma for a suite of 95 CECs. For the study set of 95 CECs, 82 were detected above the corresponding minimum reporting limit (MRL) in the primary effluent. 14 CECs were not detected in any WRRF samples. 18 of the studied 95 CECs were fully (100%) removed by full-scale WRRF biological treatment. 64 of the 95 studied CECs were found to exist in the secondary effluent at residual concentrations above MRL.